Pengaruh Partai Politik terhadap Konstruksi Pemikiran M. Natsir - Hafnita Sari Dewi Lubis; Muhammad Ihsan Syahaf Nasution (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
The purpose of this study is to analyze the role of M. Natsir in Indonesian politics. In addition, to find out the role of political parties in Natsir's thinking and the impact of political parties in M. Natsir's political thought. The method used is the historical method. This method is used because to explore past data to find data that is free from prejudice, it must go through a critical analytical process and objectivity can be maintained. With this method, it can be found that Natsir's many efforts in formulating Islam as the basis of the state and his efforts to obtain justice in the development of a region. This was done of course because of the support from various groups, both civilian, military, and political parties such as the Masyumi Party and the Indonesian Socialist Party.